Khazanah Tasawuf Nusantara: Telaah Atas Pemikiran Maqamat Tasawuf Nawawi Al-Bantani Dalam Kitab Salalim Al-Fudhala’ - Zulfikar, Eko (Spiritualita, 2020)
Not a few of the archipelago gave birth to world-class scholars. One of them is Muhammad Nawawi al-Bantani, from Serang, Banten. He was a scholar who was very productive in writing, and many of the books he wrote were in Arabic. Among his phenomenal works is in the field of Sufism, Salalim al-Fudhalaâ’ ala Hidayat al-Adzkiya ‘ila Thariq al-Auliyaâ’. This paper tries to explore the thoughts of the mysticism of Nawawi mysticism in the book Salalim al-Fudhalaâ’. With pure literature study and intertextuality data analysis, it was found that the thoughts of Nawawi Sufism can be classified into nine parts, namely repentance, qana'ah, zuhud, studying the knowledge of Shariâ’a, practicing the Sunnah of the Prophet, tawakal, sincerity, ‘uzlah (isolating oneself), and take advantage of time. The concept of Maqamat Tasawuf Nawawi is an implementation of the basic concept of Sufism, namely piety and integration between Shari'a, tarekat and essence.